PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN KONSUMEN DENGAN MEDIASI VARIABEL KEPUTUSAN PEMBELIAN PADA INDUSTRI MAKMUR JAYA DI BESUKI - Zubairi, Ahmad; Ediyanto, Ediyanto; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Marketing is the process of identifying, creating and communicating value, and maintaining customer-satisfying relationships to maximize company profits. Along with economic growth and increasingly sophisticated technology, companies have emerged that create products and services that can meet the needs of the community. The price and quality of the products produced by the company are very important in determining consumer decisions to make purchases, so that consumers can be satisfied and interested in repurchasing the products produced by the company. The purpose of this study is to analyze and examine the effect of price and product quality on consumer satisfaction in the prosperous industry through purchasing decisions. The population in this study were all consumers who bought tofu in the prosperous industry in the Besuki area. The sampling technique used is random sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that price has a significant positive effect on purchasing decisions, product quality has a significant negative effect on purchasing decisions, price has a significantly positive effect on consumer satisfaction, product quality has a significant negative effect on consumer satisfaction, and purchase decisions significant positive effect on consumer satisfaction. The results of the indirect effect hypothesis test show that the price variable on consumer satisfaction through purchasing decisions has a significant positive effect and product quality on consumer satisfaction through purchasing decisions has a significant negative effect.